A case of tethered cord syndrome in an elderly man - Morizawa, Yosuke (Hinyokika kiyo. Acta urologica Japonica, 2014)
A 71-year-old man had been under treatment for nocturia with an anti-cholinergic agent at a urologic clinic for the last 2 years. Because the symptoms did not improve, he was referred to our hospital for treatment of urinary retention. Based on the findings of a neurological examination, we suspected the presence of a neurogenic bladder due to sacral lesions. Moreover, magnetic resonance imaging indicated tethered cord syndrome (TCS) due to spinal cord lipoma. He underwent surgical treatment for TCS, which improved storage function, but not voiding function. Generally speaking, we believe that early diagnosis of TCS facilitates early surgery that can prevent the development of neurogenic disorders. In the present case, if the neurological findings had been appropriately assessed and cystometry/urodynamic studies had been performed at an earlier stage, a prompt diagnosis could have been made and surgery could have been performed earlier as well. Although adult cases with TCS are rarely observed, TCS should be considered as one of the causes of intractable lower urinary tract symptoms